Rotating Equipment : Maintenance and Troubleshooting. - Watterson, James M. (Engineering technology collection., 2019)
This book has been written on the back of Dr. Watterson's experience in working with over 20 oil refineries and petrochemical and fertilizer industries worldwide, which spans over 30 years. Every aspect of rotating equipment is explored, from turbines, both gas and steam, compressors, pumps to the use of predictive maintenance equipment. Included in this book is an in-depth explanation of predictive maintenance techniques, such as ultrasound testing, eddy curves, visual testing techniques, such as stroboscope, liquid penetrant, and vibration monitoring. Dr. Watterson also describes clearly the value of online condition-based monitoring of rotating equipment. The primary objective of this book is to show the way to reduce cost and frequency of planned maintenance by detection of abnormalities on equipment's operating and preset performance parameters.